2021
DOI: 10.3390/ma14071666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Aging on the Mechanical Properties of High Tenacity Polyester Yarn

Abstract: Textile materials produced from a high tenacity industrial polyester fiber are most widely used in the mechanical rubber goods industry to reinforce conveyor belts, tire cords, and hoses. Reinforcement of textile rubber undergoes a vulcanization process to adhere the textile materials with the rubber and to enhance the physio-mechanical properties of the product. The vulcanization process has an influence on the textile material being used as a reinforcement. In this work, the effects of aging temperature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…One of the most important mechanisms for degradation is physical ageing due water or wet ageing. Lemmi et al studied the nature of physical ageing of polycrystalline PET, varying the temperature and duration of ageing, and then compared how ageing directly affects fibre strength ( Figure 2 ) [ 32 ].…”
Section: Fragments Of Plastics and Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most important mechanisms for degradation is physical ageing due water or wet ageing. Lemmi et al studied the nature of physical ageing of polycrystalline PET, varying the temperature and duration of ageing, and then compared how ageing directly affects fibre strength ( Figure 2 ) [ 32 ].…”
Section: Fragments Of Plastics and Polymersmentioning
confidence: 99%
“…The parameters of thermal ageing significantly affect the mechanical and physical properties of the samples. In summary, the strength and thermal elongation are inversely proportional to the ageing temperature [ 32 ].…”
Section: Fragments Of Plastics and Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no significant changes observed in the percentage elongation at break of fabric samples aged at 140 on the thermal aging temperature and time; in determining the tensile properties of the fabric, the fabric's fiber composition plays a major role. EP fabric is a composition of yarn made from polyester fiber and polyamide 66; these fibers' mechanical properties depend on the aging temperature [21,27].…”
Section: Effect Of Thermal Aging Parameters On the Percentage Elongation Of Woven Fabricmentioning
confidence: 99%
“…The influence of the fabric's weave structure on the mechanical properties of the multi-layer woven fabrics used for conveyor belt reinforcement was also investigated by Witczak et al [20]. The effect of thermal aging parameters on the physical and mechanical properties of the yarns used to produce a carcass of the textile-reinforced conveyor belt was investigated by Lemmi et al [21]; the study revealed that the percentage elongation of the polyester yarns was adversely affected under high thermal aging temperature with a minimum aging duration, and the yarn's tenacity has deteriorated at higher aging temperature (220 • C). Kabzinski [22] presented basic information about the conveyor belt design and woven fabric structure used for the purpose of conveyor belt reinforcement.…”
Section: Introductionmentioning
confidence: 99%